2022
DOI: 10.3390/jcm11164815
|View full text |Cite
|
Sign up to set email alerts
|

Does Elevated Pre-Treatment Plasma PD-L1 Level Indicate an Increased Tumor Burden and Worse Prognosis in Metastatic Colorectal Cancer?

Abstract: Background: Programmed death-ligand 1 (PD-L1) and programmed cell death protein 1 (PD-1) have been reported as possibly favorable prognostic factors in colorectal cancer (CRC). However, their longitudinal effect is unknown. Methods: A pilot study was performed to investigate whether baseline PD-1/PD-L1 levels are associated with further laboratory changes and/or shorter survival. Results: A total of 506 laboratory measurements from 37 metastatic CRC patients were analyzed. The baseline plasma PD-1 and PD-L1 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Consistent with our findings, the association of sPD-L1 with disease advancement parameters has been identified in various other tumors: in aggressive bladder cancer ( 55 ), advanced (ccRCC) ( 12 ), and gastric cancer ( 35 ). Baseline sPD-L1 has proven to be a reliable tumor marker in metastatic breast cancer ( 48 ) and has been linked to rapid metastatic progression in metastatic ccRCC ( 51 ), as well as to the size of metastases in colorectal cancer ( 56 ). Elevated initial sPD-L1 levels have been associated with poorer prognosis in ccRCC ( 57 ), soft tissue sarcomas ( 28 ), pancreatic adenocarcinoma ( 58 ), lung cancer ( 49 , 59 ), hepatocellular carcinoma ( 36 ), and lower-grade glioma ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our findings, the association of sPD-L1 with disease advancement parameters has been identified in various other tumors: in aggressive bladder cancer ( 55 ), advanced (ccRCC) ( 12 ), and gastric cancer ( 35 ). Baseline sPD-L1 has proven to be a reliable tumor marker in metastatic breast cancer ( 48 ) and has been linked to rapid metastatic progression in metastatic ccRCC ( 51 ), as well as to the size of metastases in colorectal cancer ( 56 ). Elevated initial sPD-L1 levels have been associated with poorer prognosis in ccRCC ( 57 ), soft tissue sarcomas ( 28 ), pancreatic adenocarcinoma ( 58 ), lung cancer ( 49 , 59 ), hepatocellular carcinoma ( 36 ), and lower-grade glioma ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In metastatic ccRCC higher concentrations of sPD-1 tended to correlate with advanced cancer stage as well ( 51 ). For patients with metastatic colorectal cancer (mCRC), soluble PD-1, similar to soluble PD-L1, was linked to clinically worse levels of various peripheral blood parameters and metastatic tumor burden ( 56 ) and predicted systemic inflammation in pancreatic cancer ( 65 ). Although our data reflects finding between pretreatment sPD-1 levels and tumor progression in other cancers, the precise mechanism of the role of sPD-1 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CRC, tumoral expression of the membrane-bound receptor form of PD-L1 (mPD-L1) is a rare characteristic strongly associated with PD-1-positive lymphocytic infiltrates and deficiency in mismatchrepair systems, which are markers predicting high immunogenicity and responsiveness to anti-PD-1/PD-L1 therapies [52]. However, a previous study by Dank et al showed that high levels of the PD-L1 soluble form (sPD-L1) in plasma were significantly associated with increased tumor burden and shorter disease-specific survival and progression-free survival in metastatic CRC patients [25]. Similarly, Omura et al confirmed the prognostic potential of both sPD-L1 and mPD-L1 in stage I-III CRC patients, where elevated pre-operative sPD-L1 levels were significantly correlated with lymphatic invasion, and both high tumoral mPD-L1 and elevated preoperative sPD-L1 were significantly associated with shorter overall survival and disease-free survival [24].…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 protein can also be found on malignant cells, providing an immune evasion mechanism exploited by different tumor types [23], including melanoma, non-small-cell lung cancer, ovarian and breast, and gastrointestinal malignancies. In CRC, determining the serum levels of PD-L1 may have prognostic significance since previous studies showed a negative correlation of PD-L1 serum levels in CRC patients with overall survival [24,25].…”
Section: Introductionmentioning
confidence: 99%